Behaviour of precast reinforced concrete structural wall systems subjected to in-plane lateral loading. (15th August 2021) - Singhal, Shubham; Chourasia, Ajay; Kajale, Yogesh; Singh, Dirgha
Highlights: Precast wall-column system (PWCS) with loop bars evaluated under cyclic loading. Precast double leaf wall system (PDLS) evaluated under cyclic loading. Loop bars in PWCS found to be effective, without showing rupture during the test. No debonding between cast-in-situ and precast concrete observed in PDLS. PWCS and PDLS delivered eminent seismic characteristics with no significant damage. Abstract: Precast structural walls are commonly adopted as lateral load resisting elements in buildings, owing to improved quality and rapid construction. However, they suffer demerits in terms of weight and joint connections, which have strong influence on global behaviour of the building and calls for detailed investigation. This paper evaluates behaviour of two different types of precast reinforced concrete structural wall systems viz. precast wall-column system and precast double leaf system. The former comprises a precast wall connected with precast hollow columns through loop bars, while the latter comprises two precast panels with hollow core, which is casted with in-situ concrete. Both the wall systems were subjected to lateral load under displacement controlled cyclic mode and hysteretic characteristics were assessed in detail in terms of damage pattern and various seismic characteristics. Quantified performance limits were co-related with the performance acceptance criterion specified in codes. Finite element numerical analysis was executed to verify and compare the behavior of developed precast structural wall systems with the experimental results. No significant damage in precast wall-column system was observed, except few flexural cracks and separation at wall-column joint. Precast double leaf system experienced severance near the toe region along with uplift of precast panels, while the wall surface was crack free. Both the systems exhibited competent seismic parameters, thus enhancing confidence to accept and emulate developed precast structural wall systems, owing to their several advantages over conventional structural walls.